2020
DOI: 10.1111/bcpt.13502
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord blood serum attenuates gentamicin‐induced liver toxicity by restoring peripheral oxidative damage and inflammation in rats

Abstract: is an aminoglycoside antibiotic. Despite its clinical effects, its application has been restricted due to adverse side effects. The application of this antibiotic is a prevalent cause of acute renal failure in about 10 to 20% of the consumers. 1 Apart from the renal effects, GM also has hepatic effects that induce apoptosis and increase the activity of the reactive oxygen species (ROS). 2 Acute hepatic deficiencies caused by medication are associated with the rapid loss of hepatic function as well as high mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Exosomes derived from umbilical cord blood stem cells have been reported to ameliorate IL‐6‐mediated acute liver injury 22 . Human umbilical cord serum can reduce gentamicin‐induced hepatotoxicity by restoring peripheral oxidative damage and the inflammatory response in rats 23 . Accidentally, we found that umbilical cord serum has a certain inhibitory effect on HCC cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Exosomes derived from umbilical cord blood stem cells have been reported to ameliorate IL‐6‐mediated acute liver injury 22 . Human umbilical cord serum can reduce gentamicin‐induced hepatotoxicity by restoring peripheral oxidative damage and the inflammatory response in rats 23 . Accidentally, we found that umbilical cord serum has a certain inhibitory effect on HCC cells.…”
Section: Discussionmentioning
confidence: 69%
“…22 Human umbilical cord serum can reduce gentamicin-induced hepatotoxicity by restoring peripheral oxidative damage and the inflammatory response in rats. 23 Accidentally, we found that umbilical cord serum has a certain inhibitory effect on HCC cells. To further analyse human umbilical cord serum and verify its effect on tumour biology, we collected and measured the bioactivity of human umbilical cord serum by proteomics biotechnology.…”
Section: Discussionmentioning
confidence: 91%